Results of laboratory diagnosis of rabies in herbivores (cattle and horses): A retrospective study - De Castro Barrosa, Noelle [UNESP]; Langoni, Hélio [UNESP]; Victória, Cassiano [UNESP]; Menozzi, Benedito Donizete [UNESP]; Mantovan, Karine Bott [UNESP]; Latosinski, Giulia Soares [UNESP]; Joaquim, Sâmea Fernandes [UNESP] (My University, 2018)
Rabies is a zoonosis of extreme importance to public health. Specifically in herbivores it causes economic losses, considering its lethality. The diagnosis provides information to describe the epidemiology of the disease in the regional study. For this purpose, a survey of Central Nervous System (CNS) materials, received for diagnosis in the Center-West region of the State of São Paulo, by the Zoonosis Diagnostic Service (SDZ), Faculdade de Medicina Veterinária e Zootecnia (FMVZ) - UNESP-Botucatu-SP. In the period from 2001 to 2015, a total of 643 samples were analyzed, being 489 (76.05%) of the bovine species, with 68 (13.9%) positive samples and 154 (23.95%) of the equine species with 17 (11.3%) positive. For the analyzed bovine samples, sensitivity and specificity values of the fluorescent antibody test (FAT) were 88.24 and 99.52% respectively and for equines, 47.06 and 100.0%. The frequency of samples received by species, month, and year and the results of the diagnostic tests recommended by the World Health Organization (WHO), fluorescent antibody test (FAT) and the mouse inoculation test (MIT), were analysed.
Resultados do diagnóstico laboratorial de raiva em herbívoros (bovinos e equinos): estudo retrospectivo
Keywords: Diagnosis; Herbivores; Rabies; Surveillance